Loss, Gain, and Equivalence in the Translation of Culture-loaded Words in To Live: A Novel (International Journal of Language, Literacy and Translation, 2025)
Translating Culture-loaded Words from Chinese to English presents profound challenges due to their intrinsic cultural specificities. This study critically examines these challenges within To Live: A Novel, employing a novel text analysis methodology based on Bassnett's (2013) and Jakobson’s (2012) definitions of loss, gain, and equivalence in translation. Our findings reveal distinctive patterns of loss and gain that are not unique to the narrative style and cultural context of the novel but also offer broader insights into the dynamics of cultural translation. Despite the expertise of skilled translators in Chinese culture, achieving complete equivalence remains elusive, underlining significant discrepancies that persist in cross-cultural contexts. The study explains these complex translation dynamics and detailed strategies to enhance cultural fidelity and equivalence in such translations. The findings can assist in bridging the cultural gaps in English translation of Chinese novels more effectively and have some implications for Chinese literary translators.